2021
DOI: 10.3390/ijerph18147639
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, Health Behaviors, and Social Relations among Chinese Immigrants Living in Spain

Abstract: This study aims to identify acculturation experiences about social relations and health behaviors of first-generation Chinese immigrants in the South of Spain, including food patterns, physical exercise, and tobacco and alcohol use. A phenomenological qualitative study was conducted using semi-structured interviews, informal conversations, and field notes. All data were analyzed under the Berry’s Model of Acculturation. A total of 133 Chinese immigrants were included. Our findings show that separation was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(34 reference statements)
1
4
0
1
Order By: Relevance
“…The main meals included breakfast, lunch, and dinner, and this custom was maintained after arriving in Portugal. Even so, breakfast is where the great Westernization of eating habits can be noted, as reported in other countries such as Spain, the United States, and Australia [1,25,26]. Participants in the present study reported preferring to have a markedly Western breakfast instead of the typical Eastern one as it is more practical and easier to prepare.…”
Section: Discussionsupporting
confidence: 60%
“…The main meals included breakfast, lunch, and dinner, and this custom was maintained after arriving in Portugal. Even so, breakfast is where the great Westernization of eating habits can be noted, as reported in other countries such as Spain, the United States, and Australia [1,25,26]. Participants in the present study reported preferring to have a markedly Western breakfast instead of the typical Eastern one as it is more practical and easier to prepare.…”
Section: Discussionsupporting
confidence: 60%
“…Youths with a Chinese background are, as mentioned, the only exception. Language distance to Spanish and Catalan and high levels of ethnic endogeneity in their social networks found by recent studies based on Spain (Badanta et al 2021a;2021b;Wang 2021) are plausible explanations for this.…”
Section: Discussionmentioning
confidence: 94%
“…Being aware that immigrants' cultural identity influences their interpretation of health-related messages from the host society, can help us understand their health-related behaviors. 55 Recent evidence shows that acculturation, mostly capturing immigrants' birthplace and the duration of their stay in the host country, is associated with their health-related behaviors and health outcomes. 56,57 Chinese immigrants' acculturation influences chronic condition management in a complex way, which is shaped by various factors, such as their cultural background, their goals for acculturation, and the pressure they feel to assimilate.…”
Section: Discussionmentioning
confidence: 99%